2017
DOI: 10.1155/2017/7805058
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulations in Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is a chronic complication of diabetes and the most common cause of end-stage kidney disease. It has been reported that multiple factors are involved in the pathogenesis of DN, while the molecular mechanisms that lead to DN are still not fully understood. Numerous risk factors for the development of diabetic nephropathy have been proposed, including ethnicity and inherited genetic differences. Recently, with the development of high-throughput technologies, there is emerging evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 64 publications
1
45
0
1
Order By: Relevance
“…Ethnicity and differences in inherited genetics have been proposed as responses to the damage in both kidneys and heart due to diabetes (34,60). The molecular basis underlying these complications remains unknown (34). Recent evidence has suggested important roles of epigenetics leading to DN and DCM.…”
Section: Introductionmentioning
confidence: 99%
“…Ethnicity and differences in inherited genetics have been proposed as responses to the damage in both kidneys and heart due to diabetes (34,60). The molecular basis underlying these complications remains unknown (34). Recent evidence has suggested important roles of epigenetics leading to DN and DCM.…”
Section: Introductionmentioning
confidence: 99%
“…To date, research on lncRNAs has focused on the role of lncRNAs in genetics, particularly in the regulation of transcription, post-transcription or epigenetics via the biological processes of histone modification, chromatin remodelling or DNA methylation [27]. Studies have also shown that lncRNAs are involved in various diseases, including DN [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic modifications can cause changes in gene expression, without changing the DNA sequence ( Gibney and Nolan, 2010 ) and are self-perpetuating, dynamic, and reversible in response to the environment ( Beckerman et al., 2014 ). Many factors can influence epigenetic profiles, including hyperglycemia, hypoxia, and inflammation ( Lu et al., 2017 ). Epigenetic modifications can either be beneficial, or hamper GEnC function by changing the transcriptome, resulting in GEnC dysfunction and potentially disturbed cross-talk and pathogenesis of FSGS and DN.…”
Section: Epigenetic Modifications: a Potential Mechanism Involved In mentioning
confidence: 99%
“…DNA methylation can also inhibit gene expression via methyl binding proteins, which in turn recruit transcriptional co-repressors. DNA methylation at genes can modulate transcriptional elongation and alternative splicing ( Gibney and Nolan, 2010 ; Lu et al., 2017 ).…”
Section: Epigenetic Modifications: a Potential Mechanism Involved In mentioning
confidence: 99%